Restoration of contaminated aquifers : petroleum hydrocarbons and organic compounds - Testa, Stephen M. (Lewis, 2000)
This edition incorporates advanced in situ remediation and natural attenuation, and maintains the comprehensive structure that was used in the first edition. It emphasizes the remediation of non-aqueous phase liquids, dense non-aqueous phase liquids, and the growing role of natural attenuation.